Effect of optimal cycling repeated-sprint combined with classical training on peak leg power in female soccer players - Gmada, N.; Farhani, Z.; Bouhlel, H.; Marzouki, H.; Tabka, Z.; Shephard, R.; Bouhlel, E. (Isokinetics and Exercise Science, 2014)
BACKGROUND: Muscle power is one of the most important factors influencing sport performance. Despite the variety of training methods used in the literature, more individualised, varied and enjoyable methods are needed to enhance muscle peak power in soccer. OBJECTIVE: To assess the effect of short-sprint cycle ergometer training on peak power output and field performance of female soccer players. METHODS: 7 female soccer players (age: 20.2 ± 1.5 (years); body mass: 55.1 ± 6.1 (kg); height: 1.61 ± 0.06 (m)) served as an experimental group, and seven female soccer players (age: 19.4 ± 1.5 (years); body mass: 65.2 ± 6.1 kg; height: 1.69 ± 0.08 m) as a control group. Peak power output during a cycle ergometer force-velocity test and field performance (5-jump test and speeds over 10, 20 and 30 m) were assessed both before and after training (3 months duration, with 3 sessions per week). Each training session comprised 2 series of 15 sprints, separated by a 15 min recovery interval. Individual sprints were of 5 sec duration, at the optimal pedalling velocity for the subject (100-110 rpm) and against the optimal frictional loading equal of the subject (7.5%-8.5% of body mass); a recovery period of 55 sec was allowed between sprints. RESULTS: The training regimen induced gains of peak power (p< 0.05). There were also gains in 5-jump (p< 0.01), and 20 and 30 m sprint velocities (p< 0.01). Findings in the control participants remained unchanged. CONCLUSION: When combined with traditional soccer training, repeated short sprints on a cycle ergometer offer an effective strategy for enhancing leg power in female Tunisian soccer players. ABSTRACT FROM AUTHOR